Behaviour and Velocity of Free Falling Balls in Fluid - M. V. Krautsou; A. M. Krautsou (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper gives further interpretation of resistance law in case when single balls are falling in fluid and also presents research of free falling balls behaviour depending on a resistance force value.On the basis of general resistance law a formula for calculation of free falling single ball velocity is suggested in the paper.